2014
DOI: 10.1254/jphs.13r12cp
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Injured Renal Tubules

Abstract: Abstract. Acute kidney injury (AKI), clinically defined by high serum creatinine and low urine flow, has many complicated pathophysiological features including tubular and glomerular injury. Although renal tubules are thought to be constituted by highly differentiated epithelial cells, it is possible to repair injured nephrons by the healing process. Several studies have revealed that AKI, especially AKI caused by ischemia/reperfusion injury or nephrotoxic medication, depends on a number of factors, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Dedifferentiation of injured tubular cells [following detachment of injured epithelium] the basement membrane of tubules is covered by mesenchymal cells that repair tubular damage (3). Immigration of bone marrow derived cells to the kidney and participates in renal regeneration [34]. These results are confirmed with other research that showed the protective impact of E. sativa against nephrotoxicity [35] [36].…”
Section: Discussionsupporting
confidence: 85%
“…Dedifferentiation of injured tubular cells [following detachment of injured epithelium] the basement membrane of tubules is covered by mesenchymal cells that repair tubular damage (3). Immigration of bone marrow derived cells to the kidney and participates in renal regeneration [34]. These results are confirmed with other research that showed the protective impact of E. sativa against nephrotoxicity [35] [36].…”
Section: Discussionsupporting
confidence: 85%
“…Tozzi et al outlined how PP significantly reduces tissue antigen expression of soluble intracellular adhesion molecule-1 (sICAM-1) and pro-inflammatory cytokine (TNFα, IL-2 and IL-1β) compared to SCS controls, resulting in the reduction of leucocyte stimulation (particular neutrophils) and a decrease in postreperfusion activated inflammation-mediated acute-phase proteins that are responsible for ischemia/reperfusion injury (IRI). Many authors have stressed the correlation between IRI, cell apoptosis, delayed graft function (DGF) and chronic renal failure [22,23]. Apoptosis is a reversible programmed cell death [24].…”
Section: Dynamic Perfusion Apoptosis and Inflammationmentioning
confidence: 99%
“…Recovery from ischemic and nephrotoxic AKI depends on regeneration of damaged tubular cells. Renal stem or progenitor cells outside the nephron migrate into the damaged nephrons and then regenerate the tubules (1,2). Several studies suggest that there is a very delicate and dynamic relationship between tissue repair and progression or regression of renal injury (2).…”
Section: öZmentioning
confidence: 99%